2016
DOI: 10.1186/s13052-016-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and migraine is there a possible comorbidity?

Abstract: The association between migraine and stroke is still a dilemma for neurologists. Migraine is associated with an increased stroke risk and it is considered an independent risk factor for ischaemic stroke in a particular subgroup of patients. The pathogenesis is still unknown even if several studies report some common biochemical mechanisms between these two diseases. A classification of migraine-related stroke that encompasses the full spectrum of the possible relationship between migraine and stroke includes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
0
18
1
4
Order By: Relevance
“…Due to a lack of prior clinical information, we cannot exclude other aetiologies for the ischaemic events, e.g. if they are due to environmental or lifestyle stresses, vasoconstrictive drugs used as a prior treatment or if another gene mutation not tested is the cause [45,47,48]. Another heterozygous gene mutation was identified in ATP1A2 in CAD-400 that is known to cause familial hemiplegic migraine type 2 (FHM2) (MIM#602481).…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of prior clinical information, we cannot exclude other aetiologies for the ischaemic events, e.g. if they are due to environmental or lifestyle stresses, vasoconstrictive drugs used as a prior treatment or if another gene mutation not tested is the cause [45,47,48]. Another heterozygous gene mutation was identified in ATP1A2 in CAD-400 that is known to cause familial hemiplegic migraine type 2 (FHM2) (MIM#602481).…”
Section: Discussionmentioning
confidence: 99%
“…The territory of the posterior circulation is mostly involved (70-82%). Young women are more affected, probably with a bias of selection, since the migraine with aura by itself is more frequent in this population 31. The imaging examinations more often reveal single or multiple small lesions limited to an unique vascular territory 35.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, subgroup analyses have revealed significant interactions for gender, age, smoking and oral contraceptive use with higher risk estimates in women, patients below age 45 years, smokers and women using oral contraceptives. 3 5 …”
Section: Introductionmentioning
confidence: 99%
“… 2 , 4 6 , 11 These mechanisms are shared with other vascular diseases and recently, migraine has also been associated with increased risk of ischemic heart disease 12 , 13 and it has been suggested that migraine should be viewed as a systemic disorder affecting the endovascular system. 5 , 6 , 11 However, while a number of studies have shown an association between migraine with aura and ischemic stroke, evidence is less consistent for hemorrhagic stroke, transient ischemic attacks (TIA), and ischemic heart disease as well for migraine without aura. In addition, many of the previous studies have only included a small number of confounding factors.…”
Section: Introductionmentioning
confidence: 99%